Bioactivity of Indonesian mahogany, Toona sureni (Blume) (Meliaceae), against the red flour beetle, Tribolium castaneum (Coleoptera, Tenebrionidae) - Sahana Parvin; Xin-Nian Zeng; Touhidul Islam (Revista Brasileira de Entomologia, 2012)
Bioactivity of Indonesian mahogany, Toona sureni (Blume) (Meliaceae), against the red flour beetle, Tribolium castaneum (Coleoptera, Tenebrionidae). The insecticidal activity of Toona sureni (Blume) Merr. was evaluated considering repellency, mortality and progeny production of F1 adults of Tribolium castaneum (Herbst, 1797) (Coleoptera, Tenebrionidae). Dried extract of seeds of T. sureni was dissolved in acetone to prepare solution of various concentrations (0.5, 1.0, 2.5 and 5.0%). To test for repellency, the insects were exposed to treated filter paper. Mortality of larvae, pupae and adults was evaluated by the treatment of spraying the insects with different concentrations of T. sureni extract. Residual effect of the extract was also evaluated considering the production of progeny of F1 adults. The highest repellency (93.30%) of T. castaneum occurred at the highest concentration (5.0% suspension of T. sureni); while the lowest (0.0%) repellency occurred at 0.5% suspension after 1 day of treatment. The highest mortality against adults (86.71%), larvae (88.32%) and pupae (85%) occurred at 5% suspension at 8 days after application. There was a negative correlation between the concentrations of T. sureni and the production of F1 adult's progeny of T. castaneum. The highest number of progeny (147) of T. castaneum occurred in the control at 7 days after treatment; and the lowest number of progeny (43) occurred at 5.0% concentration in 1 day after treatment. The results show that T. sureni is toxic to T. castaneum and has the potential to control all stages of this insect in stored wheat.